Dynamics superposition mechanism analysis of the overlapped tunnel groups during the shield tunnel undercrossing. Issue 5 (October 2020) - Zeng, Qinghe; Ming, Weihua; Luo, Jin; Zhou, Cuiying; Liu, Zhen
Abstract: Studies on superposition mechanism analysis of the old-new overlapped tunnel systems during the undercrossing process are still exploratory. Based on the viscoelastic-plastic theory of the underground structure and nonlinear evolution model of tunnel deformation and instability, the nonlinear dynamic evolution model, energy evolution model, and failure criterion of the three-dimensional (3D) tunnel system are established. The temporal and spatial superposition mechanism of the old-new overlapped tunnel system during the undercrossing process is quantitatively analyzed. The spatial expansibility and temporal continuity of the superposition mechanism are also verified. The intersecting line formula and its expansion formula of the cylinder and cone calculate the position, boundary, and volume of the superposition area. Based on the disturbed state concept theory, the disturbed function during the new shield tunnel undercrossing is theoretically derived. This study is significant for the quantitative analysis and control of the overlapped tunnel stability during the undercrossing process.